Nondestructive evaluation of thermal barrier coatings - Tan, Bo (2017)
Thermal barrier coatings at high temperature thermal cyclic oxidation generate stress concentration and result in coating failure, which can endanger the engine during operation. Regular nondestructive inspection of their quality condition has received increasing attention. This project is aimed to investigate the thermal cyclic oxidation behaviours of TBC system and evaluate thermal barrier coating during thermal cycling by optimised nondestructive evaluation techniques along with microstructure analysis using scanning electron microscopy. The internal microstructure and exterior surface morphology of an unconventional TBC sample coated by ESAVD were investigated using two different laboratory X-ray CT scan systems. As a result, an image resolution of 0.6 µm is achieved by Xradia XRM-500 X-ray CT, five different layers were observed in the thermal barrier coating system including a few of cracks at the interface of YSZ layer and bond coat. The thermal cyclic oxidation behaviour of conventional 7-8 wt.% YSZ air plasma sprayed TBC sample was evaluated using laser photoacoustic spectroscopy. The thickness of TGO layer of each sample after thermal cyclic oxidation was measured in a panorama BSE image using image analysis. A relationship was found between signal energy and TGO thickness, illustrating that signal energy decreases with the increasing TGO thickness. A physical model was studied to estimate the influence of crack inside TGO on signal attenuation, which indicated that the signal energy reduction is due to a combination of laser reflection at interfaces, laser attenuation by TGO layer and ultrasound reflection at interfaces. In addition, the position of the presence of crack inside of TGO alters the remainder of signal energy, where crack presented near the interface of TGO layer and bond coat attenuates more signal energy. Study on amplitude attenuation in a bond coat only sample has confirmed that ultrasound signal was generated in TGO layer which works as a constrained surface layer facilitate the laser ultrasonic generation at early oxidation stage. It is shown that the increasing thickness of TGO layer increased the attenuation of laser irradiation, and the increasing number of cracks in TGO layer increased the laser reflection at crack/TGO interfaces. The analysis of asymmetric electrode geometry effect on YSZ material using the finite element simulation was demonstrated, subsequently the findings of which were verified via electrochemical impedance spectroscopy using a set of YSZ ceramic bulk samples with asymmetric electrodes geometry. It is shown that asymmetric electrode geometry results in non-uniform current distribution in the simulated model. The direction of current diverges from the centre to the side by the radial electrical potential and then gradually return to the direction perpendicular to the surface. An equivalent electrode area is calculated which can be used to fix the influence of asymmetric electrode geometry in impedance spectroscopy measurement by replacing the area of applied conductive paint in the calculation. A linear relationship is revealed between the ratio of equivalent area to applied electrode area and the resistance of simulated model. The gradient of their plots is proportional to the thickness of the sample. Based on the relationship, a method is proposed to estimate the resistance of a sample with a known asymmetric electrode geometry via an inverse operation.